2008
DOI: 10.1016/j.jelechem.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and application of carbon film electrodes in room temperature ionic liquid media

Abstract: Carbon film electrodes have been characterised in the room temperature ionic liquids, 1-butyl-3-methylimidazolium bis(trifluoromethane)sulfonimide (BmimNTF 2 ), 1-butyl-1-methylpyrrolidinium bis(trifluoromethane)sulfonimide, (BpyrNTF 2 ) and 1-butyl-3-methylimidazolium nitrate (BmimNO 3 ), by cyclic voltammetry and electrochemical impedance spectroscopy. The electrochemical behaviour of the ionic liquids depended on both cation and anion of these electrolytes. Oxygen reduction is clearly visible at carbon film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…We found two theoretical [8,9] and four experimental [17][18][19][20] articles dealing with double-layer capacitance -impedance -pztc issues which are relevant for electrodes in ILs. However, the theoretical papers derive capacitance-potential curves without the mentioning of the dynamics of the double-layer rearrangements expressed by the existence of the CPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found two theoretical [8,9] and four experimental [17][18][19][20] articles dealing with double-layer capacitance -impedance -pztc issues which are relevant for electrodes in ILs. However, the theoretical papers derive capacitance-potential curves without the mentioning of the dynamics of the double-layer rearrangements expressed by the existence of the CPE.…”
Section: Discussionmentioning
confidence: 99%
“…[17,19,21] -having a well-defined clean surface, the electrode materials (carbon [17], glassy carbon [17,21], gold [17] and platinum [21]) are polycrystalline. On the basis of aqueous electrochemistry experience, interfacial studies with single crystals of well-defined surfaces yield better-defined results than polycrystalline ones.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from in aqueous solutions, PNR can also be successfully synthesized in non-aqueous solutions, for example in acetonitrile with the addition of Bu 4 NClO 4 at Pt electrodes [22,49] or from room temperature ionic liquids (RTIL) such as 1-butyl-3-methylimidazolium bis(trifluoromethane)sulfonimide, 1-butyl-1-methylpyrrolidinium bis(-trifluoromethane) sulfonimide, and 1-butyl-3-methylimidazolium nitrate at carbon film electrodes [50,51]. However, the last case showed that the applied potential is a crucial point: it was observed that PNR dissolved when potentials were more positive than þ 0.5 V. Moreover, such films were much thinner than those prepared in aqueous solutions since the polymerization of NR in the RTILs occurred in a slightly different way to those in aqueous solutions, due to the different solvent properties.…”
Section: Polymerization Of Neutral Redmentioning
confidence: 99%
“…Immobilisation of enzymes in hydrophilic sol-gel matrixes and ionic liquids has yielded desired stability and direct electron transfer from enzyme electrodes [103][104][105][106][107]. Biomaterials based on novel phospholipid polymers with unit imitating biomembrane have been developed.…”
Section: Discussionmentioning
confidence: 99%